Changes in the rubber morphology caused by the interaction with bitumen - Peralta, J. (2010)
It is estimated that about 10 kg of tires are discarded per inhabitant annually. This residue can be reused as a constituent of pavements in the form of asphalt rubber (AR) binder. The use of bitumen modified with crumb rubber contributes for a sustainable development of road infrastructures through: (i) the definition of an efficient final destination for the used tires of cars and trucks; (ii) the improvement of the performance of the resulting material used in the pavement. However, the materials which constitute these AR binders and the physicochemical changes in the binder during the production of the AR are not sufficiently characterized. Thus, the main objective of this study is to characterize the changes in the morphology of the rubber particles due to the interaction with three different bitumens during the production of the ARs. The studied bitumens were selected from the same origin and obtained in the same distillation column. Initially, the bitumens were left to interact with 17.5% of crumb rubber by mass of AR binder. After that, a modified “Basket Drainage Method” was used to divide the residual bitumen and the rubber of the AR binder. The recovered rubber (RR) particles from the AR binders, and the ones filtered (FR) from the residual bitumens, were then observed in an optical microscope, being measured and weighted. The morphology of the crumb rubber particles was assessed by macroscopic and microscopic observation, and their percentages of depolymerization (ASTM D 6814-02) were also determined. It was observed that the extent of morphological changes in the rubber particles is higher when softer bitumens are used, due to swelling, splitting, depolymerization or devulcanization and eventually repolymerization or revulcanization phenomena.